Cloning and Molecular Characterization of the phlD Gene Involved in the Biosynthesis of "Phloroglucinol", a Compound with Antibiotic Properties from Plant Growth Promoting Bacteria Pseudomonas spp. - Payal Gupta; Prasanta K. Dash; Tenkabailu Dharmanna Sanjay; Sharat Kumar Pradhan; Rohini Sreevathsa; Rhitu Rai (MDPI AG, 2023)
phlD is a novel kind of polyketide synthase involved in the biosynthesis of non-volatile metabolite phloroglucinol by iteratively condensing and cyclizing three molecules of malonyl-CoA as substrate. Phloroglucinol or 2,4-diacetylphloroglucinol (DAPG) is an ecologically important rhizospheric antibiotic produced by pseudomonads; it exhibits broad spectrum anti-bacterial and anti-fungal properties, leading to disease suppression in the rhizosphere. Additionally, DAPG triggers systemic resistance in plants, stimulates root exudation, as well as induces phyto-enhancing activities in other rhizobacteria. Here, we report the cloning and analysis of the phlD gene from soil-borne gram-negative bacteria-Pseudomonas. The full-length phlD gene (from 1078 nucleotides) was successfully cloned and the structural details of the PHLD protein were analyzed in-depth via a three-dimensional topology and a refined three-dimensional model for the PHLD protein was predicted. Additionally, the stereochemical properties of the PHLD protein were analyzed by the Ramachandran plot, based on which, 94.3% of residues fell in the favored region and 5.7% in the allowed region. The generated model was validated by secondary structure prediction using PDBsum. The present study aimed to clone and characterize the DAPG-producing phlD gene to be deployed in the development of broad-spectrum biopesticides for the biocontrol of rhizospheric pathogens.